Low Tidal Volume Positive End-Expiratory Pressure versus High Tidal Volume Zero-Positive End-Expiratory Pressure and Postoperative Pulmonary Functions in Robot-Assisted Laparoscopic Radical Prostatectomy - Haliloglu, Murat; Bilgili, Beliz; Ozdemir, Mehtap; Umuroglu, Tumay; Bakan, Nurten (Medical principles and practice, 2017)
Objective: The aim was to compare the effects of low tidal volume (V T ) and moderate positive end-expiratory pressure (PEEP) with high V T and zero end-expiratory pressure (ZEEP) on postoperative pulmonary functions and oxygenation in patients undergoing robot-assisted laparoscopic radical prostatectomy. Subjects and Methods: Forty-four patients were randomized into low V T -PEEP and high V T -ZEEP groups. The patients were ventilated with a V T of 6 mL/kg and 8 cm H 2 O PEEP in the low V T -PEEP group and a V T of 10 mL/kg and 0 cm H 2 O PEEP in the high V T -ZEEP group. Preoperative and postoperative spirometric measurements were done and chest X-rays were evaluated using the radiological atelectasis score (RAS). p < 0.05 was considered statistically signiﬁcant. Results: The intraoperative and postoperative arterial partial pressure of oxygen and arterial oxygen saturation values were significantly higher in the low V T -PEEP group than in the high V T -ZEEP group. At all times, the arterial-to-alveolar oxygenation gradients were significantly lower in the low V T -PEEP group than in the high V T -ZEEP group. Preoperative RAS were similar in both groups, but the postoperative RAS was significantly lower in the low V T -PEEP group (p < 0.001). Forced vital capacity, forced expiratory volume in 1 s, and peak expiratory flow rate recorded postoperatively were significantly lower in the high V T -ZEEP group (p < 0.001). Conclusions: Postoperative pulmonary functions were less impaired in patients ventilated with a V T of 6 mL/kg and 8 cm H 2 O PEEP than in patients ventilated with a V T of 10 mL/kg and ZEEP.